Linguistic Landscape of the High-End Culinary Area at GWalk Surabaya, Indonesia in a Multilingual Context - Mumtaz, Rafida; Haryono, Aura Hilda (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
This study examines the linguistic landscape of GWalk, Surabaya, Indonesia, a region characterized by a rich history of cultural diversity and high multilingualism, particularly in the high-end culinary area, which incorporates influences from Chinese, Javanese, European, and Indonesian cultures. The research collected 201 samples from GWalk using photographs as the primary data source. The analysis reveals multiple dimensions that define the linguistic landscape of high-end culinary spaces. Public signs within the area can be categorized into monolingual, bilingual, and multilingual, reflecting the distribution of languages in the GWalk linguistic landscape. The sociolinguistic aspects of the site highlight the prominence of English as a global language alongside Indonesian. Despite its high-end setting, Indonesian remains the dominant language, coexisting with Chinese, which signifies the dominant ethnic identity in GWalk Citraland, and English represents global connectivity. This interaction among languages offers a promising direction for further research. From an ethnolinguistic perspective, the local language, Javanese, is minimally represented in the linguistic landscape despite efforts to incorporate it through various forms of language modification. These findings underscore the complex dynamics of language use in a socio-culturally diverse and economically stratified urban environment.